2015
DOI: 10.1021/acsami.5b02912
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biomedical Applications of Poly((meth)acrylic acid) Brushes

Abstract: Poly((meth)acrylic acid) (P(M)AA) brushes possess a number of distinctive properties that are particularly attractive for biomedical applications. This minireview summarizes recent advances in the synthesis and biomedical applications of P(M)AA brushes and brushes containing P(M)AA segments. First, we review different surface-initiated polymerization (SIP) methods, with a focus on recent progress in the surface-initiated controlled/living radical polymerization (SI-CLRP) techniques used to generate P(M)AA brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 161 publications
0
37
0
Order By: Relevance
“…Moreover, both HA and CMCS are helpful for the adhesion and proliferation of human gingival fibroblasts. Chuan et al, 2015;Gao et al, 2017;Kabirian et al, 2019 Double bond-containing polymer Antifouling, antimicrobial, anti-fogging Contact lens Zhao et al, 2016;Kurowska et al, 2017 Polymer brush Antifouling, antimicrobial Glass, quartz, Ti Jie et al, 2015;Yu et al, 2015;Xu et al, 2017 Poly(NIPAAM) Antifouling, bactericidal Glass, PDMS, silicon Wang et al, 2016 PDA Antifouling, antimicrobial, antibacterial, antibiofilm Glass, stainless steel, plastic, gauze, catheter Liu andHuang, 2016;Su et al, 2016;Zhang et al, 2017;Zhou et al, 2017 Chitosan andderivatives Antibacterial, antibiofilm Ti, PU, PVF Li et al, 2017;D'Almeida et al, 2018;Yang M. et al, 2018 PHMB Broad-spectrum antimicrobial, bactericidal, antifouling, antibiofilm Silicone resin Su et al, 2017;Zhi et al, 2017 Responsive polymer brush Antifouling, antimicrobial, antibacterial Glass, Si, PU, MWCNTs, SiO 2 , Fe 3 O 4 Chen et al, 2010;Hu et al, 2013;Qu et al, 2015;Yan et al, 2016;Yaghoubi and Parsa, 2019 The Ti substrate was also modified by chitosan via coupling agent of triethoxysilylpropylsuccinic anhydride, and achieved the antibacterial effectiveness against E. coli and S. aureus (D'Almeida et al, 2018). Another example of chitosan-based coating on polyurethane (PU), polyvinyl fluoride (PVF) and Ti substrates was provided by Neoh group (Li et al, 2017).…”
Section: Covalent Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both HA and CMCS are helpful for the adhesion and proliferation of human gingival fibroblasts. Chuan et al, 2015;Gao et al, 2017;Kabirian et al, 2019 Double bond-containing polymer Antifouling, antimicrobial, anti-fogging Contact lens Zhao et al, 2016;Kurowska et al, 2017 Polymer brush Antifouling, antimicrobial Glass, quartz, Ti Jie et al, 2015;Yu et al, 2015;Xu et al, 2017 Poly(NIPAAM) Antifouling, bactericidal Glass, PDMS, silicon Wang et al, 2016 PDA Antifouling, antimicrobial, antibacterial, antibiofilm Glass, stainless steel, plastic, gauze, catheter Liu andHuang, 2016;Su et al, 2016;Zhang et al, 2017;Zhou et al, 2017 Chitosan andderivatives Antibacterial, antibiofilm Ti, PU, PVF Li et al, 2017;D'Almeida et al, 2018;Yang M. et al, 2018 PHMB Broad-spectrum antimicrobial, bactericidal, antifouling, antibiofilm Silicone resin Su et al, 2017;Zhi et al, 2017 Responsive polymer brush Antifouling, antimicrobial, antibacterial Glass, Si, PU, MWCNTs, SiO 2 , Fe 3 O 4 Chen et al, 2010;Hu et al, 2013;Qu et al, 2015;Yan et al, 2016;Yaghoubi and Parsa, 2019 The Ti substrate was also modified by chitosan via coupling agent of triethoxysilylpropylsuccinic anhydride, and achieved the antibacterial effectiveness against E. coli and S. aureus (D'Almeida et al, 2018). Another example of chitosan-based coating on polyurethane (PU), polyvinyl fluoride (PVF) and Ti substrates was provided by Neoh group (Li et al, 2017).…”
Section: Covalent Graftingmentioning
confidence: 99%
“…Poly(N-isopropyl-acrylamide) (PNIPAAm) is a typical thermally responsive polymer (Yaghoubi and Parsa, 2019). Its solubility responds to reversible changes of temperature with a critical temperature of 32 • C; Poly(methacrylic acid) (PMAA) is a typical pH-responsive polymer with a large number of carboxyl groups (COOH) on its repeating unit (Qu et al, 2015). The PMAA chain shows a collapsed conformation in an acidic aqueous solution and a swollen conformation in an alkaline aqueous solution.…”
Section: Covalent Graftingmentioning
confidence: 99%
“…Spherical polyelectrolyte brushes (SPB), which consist of a spherical core and densely grafted polyelectrolyte chains, have drawn much attention in catalysis [25], protein separation [26,27], and detection [28,29]. Previous works have demonstrated that SPB can be used as nanoreactors for in situ generation of metal nanoparticles due to their excellent ability of confining counterions.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, approaches have been made to combine the excellent transducing capability of SiNW FETs and the benefits from versatile polymer functionalization [44][45][46]. For instance, the switching events of brushes could be detected with FETs [47,48], dielectric materials were coated to create non-fouling surfaces [49,50], and chemical reactions were performed and transduced with polymer brush-FET systems [51,52].…”
Section: Introductionmentioning
confidence: 99%